A Review of Cocoa Drying Technologies and the Effect on Bean Quality Parameters - Banboye Frederick Dzelagha; Ngwabie Martin Ngwa; Divine Nde Bup (International Journal of Food Science)
Considering drying as a key farm-based, quality determining unit operation in the cocoa processing chain, this paper reviews recent studies in the drying methods and quality parameters of cocoa beans. Open sun, solar, oven, microwave, and freeze drying methods have been investigated at various levels in the drying of cocoa beans with objectives to improve the drying properties and final quality of cocoa beans. While an open sun dryer employs natural passive mechanisms, the solar drying methods can employ a combination of passive and active mechanisms. The oven, microwave, and freeze drying methods are fully active requiring electrical energy inputs. To improve drying rates in the open sun method, dryer materials and location of drying trays are the parameters optimized since the drying temperature depends on solar intensity. For solar dryers, materials, angles of elevation, heaters, and fans are manipulated to optimize energy absorption and drying parameters. For the oven and microwave methods, drying air properties are directly controlled by electronic systems. Moisture content, mouldiness, bean colour, pH, titratable acidity, fat content, and acetic acid concentration are the most widely evaluated bean quality parameters.